2017
DOI: 10.1002/jbm.a.36282
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel/fiber conductive scaffold for bone tissue engineering

Abstract: Hydrogel/fiber composites have emerged as compelling scaffolds for regeneration purposes. Any biorelated modification or feature may endow more regenerative functionality to these composites. In the present study, a hydrogel/fiber scaffold possessing electrical conductivity in both phases, hydrogel and fiber, has been prepared and evaluated. Fiber component possessed electrical conductivity due to the presence of polyaniline (PANi) and hydrogel fraction thanks to the presence of graphene nanoparticles. PANi ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(52 citation statements)
references
References 20 publications
2
50
0
Order By: Relevance
“…Subsequently, Jetze et al found that when integrated with oriented PCL 3D nanofibrous scaffold prepared by electrohydrodynamic printing, the gelatin hydrogel composite even increased to an impressive 54‐fold compared with hydrogel or scaffold alone (Visser et al, ). To better mimic the electrical prerequisites of natural bone, a nanofiber/hydrogel was developed with electrical conductive PCL/polyaniline fibers and polysaccharides/gelatin/graphene gels (Khorshidi & Karkhaneh, ). In vitro study showed that the nanofiber/hydrogel composite better supported the cellular response of seeded human osteoblast‐like cells (MG63) compared to hydrogel alone and are promising for bone tissue engineering.…”
Section: Integrated With Other Scaffoldsmentioning
confidence: 99%
“…Subsequently, Jetze et al found that when integrated with oriented PCL 3D nanofibrous scaffold prepared by electrohydrodynamic printing, the gelatin hydrogel composite even increased to an impressive 54‐fold compared with hydrogel or scaffold alone (Visser et al, ). To better mimic the electrical prerequisites of natural bone, a nanofiber/hydrogel was developed with electrical conductive PCL/polyaniline fibers and polysaccharides/gelatin/graphene gels (Khorshidi & Karkhaneh, ). In vitro study showed that the nanofiber/hydrogel composite better supported the cellular response of seeded human osteoblast‐like cells (MG63) compared to hydrogel alone and are promising for bone tissue engineering.…”
Section: Integrated With Other Scaffoldsmentioning
confidence: 99%
“…Gold nanoparticles (GNPs) are known to be the most promising substances for bone tissue regeneration because they promote osteogenic differentiation of MSCs [175]. Heo et al synthesized biodegradable hydrogel using GNPs and regenerated bone tissues [176].…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Some researches point out that the conductive substrates can mimic the cells’ niche in an appropriate manner and translate signals between cells through electricity . In order to supply a favor electric field for cells, conductive scaffolds emerge in various forms like three‐dimensional hydrogel, two‐dimensional fibers or sometimes particles …”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18] In order to supply a favor electric field for cells, conductive scaffolds emerge in various forms like threedimensional hydrogel, two-dimensional fibers or sometimes particles. [19][20][21] The mechanism by which ES promotes cell activities has been widely studied. For bone regeneration, the enhanced osteogenic differentiation of multipotential mesenchymal stromal cells (MSCs) under ES draws concerns.…”
Section: Introductionmentioning
confidence: 99%